CAUSES AND MEASURES TO PREVENT THE DEVELOPMENT OF FATIGUE DEFECTS RAILS - Myroshkin, V. O. (Science and Transport Progress, 2006)
Measures on warning of origin of tireless defects on the surface of rolling of head of rails are described in the article.